Journal of Clipped Words in Reader’s Digest Magazine - Lestari Simanjuntak (State University of Medan, 2012)
This study deals with Clipped Words in the “Laughter, the Best Medicine” of Reader’s Digest. The objectives of the study are to find out the types of clipped words which are used in the “Laughter, the Best Medicine” of Reader’s Digest, to find out sthe dominantly used in the whole story and to reason the dominant clipped word use in the text. The study use descriptive qualitative method. The data were collected from seventeen selected Reader’s Digest which contains the clipped word by applied documentary technique, and analyzed based on the type of clipped words namely, back clipping, fore clipping, middle clipping and complex clipping. The finding indicates that from four types of clipped words just only three types found in the “Laughter, the Best Medicine” of Reader’s Digest, back clipping, fore clipping, and a word middle clipping. Back clipping is proved to be the most dominantly used because the story in the “Laughter, the Best Medicine” of Reader’s Digest tell about human daily experience daily. Key words: Clipped words